IMPLEMENTASI KEBIJAKAN PROTOKOL KESEHATAN : PENERAPAN BUDAYA NILAI “IPK” IMAN,PENGHARAPAN DAN KASIH SEBAGAI UPAYA PENCEGAHAN COVID-19 DI STIKES RS BAPTIS KEDIRI : HEALTH PROTOCOL POLICY: IMPLEMENTATION OF THE "IPK" VALUES OF FAITH, HOPE AND LOVE AS A PREVENTION EFFORT FOR COVID-19 IN STIKES BAPTIS KEDIRI HOSPITAL - Aries Wahyuningsih (JURNAL TERAS KESEHATAN, 2022)
WHO has declared Corona Virus Disease 2019 (COVID-19) a pandemic. The government made a series of policies to deal with it. Policy (policy) is the principle or way of acting that is chosen to direct decision making. Minister of Health RI. No. HK. 01. 07/ MENKES /382/2020 regulates the Health Protocol for the Community in Public Places and Facilities in the Context of Prevention and Control of Covid-19. The purpose of writing is to describe the implementation of health protocol policies through the application of basic GPA values ??(Faith, Hope and Love) to deal with the Covid-19 pandemic at STIKES Baptist Hospital Kediri. Descriptive survey research design by conducting a literature study. The primary data source used is to collect data on the Covid 19 Task Force Team policy that is applicable and implemented at STIKES Baptist Hospital Kediri. Furthermore, the data and information obtained is done by induction, reduction and then presented in a simple form so that it is easy to understand. The implementation of the Covid-19 Health Protocol policy at STIKES Baptist Hospital Kediri was carried out using the Input, Process and Output cycle and had been carried out in accordance with the applicable standards at STIKES Baptist Hospital Kediri.